Analysis of Factors Affecting Profitability of Bank Book IV Period 2017-2019 - Fathonah, Emma Oktavia; Negoro, Dimas Angga (SAFE-Network, 2025)
Bank profitability remains a research topic without a common consensus. This study aims to identify and examine the factors that affect bank profitability. The subject of this research is banks classified as BUKU IV. Five commercial banks classified under BUKU IV were selected as the sample, with monthly observations from 2017 to 2019. The research hypotheses were tested by using panel data regression analysis with fixed effect. The results of the indicate that cost efficiency, interest rates, and exchange rates affect profitability; while credit risk, liquidity risk, capital strength, and inflation have no statistical effect.